Changing the Culture of Ordering Urine Cultures. (October 2020) - Adams, Jane; File, Thomas; England, Matthew; Reynolds, Nancy; Wells, Patricia; Politis, Paula
Abstract : Background: Inappropriate ordering of urine cultures and the resulting unnecessary use of antibiotics can lead to complications of antimicrobial therapy including resistance, adverse effects (eg, disruption of microbiome and C. difficile infection), and increased healthcare costs, as well as the erroneous determination of CAUTI in patients with Foley catheters. A retrospective analysis of patients with CAUTI revealed frequent ordering of urine cultures for conditions and symptoms not supported by current IDSA guidelines. As a result, we created an action plan to reverse the trend of inappropriate urine culture ordering. Methods: Our urine culture reduction campaign was developed with input from the infectious disease service, antibiotic stewardship team (AST), infection prevention, pharmacy, and the microbiology service. The following educational efforts were included: (1) distribution of outpatient pocket cards with communication to providers about appropriate ordering of urine cultures; (2) creation of an evidence-based order set for urinalysis and urine cultures distributed electronically as emails and screensavers on computer stations and in person via didactic sessions with physicians and nursing staff; (3) a practice pointer for staff nurses that included recommended changes to urine culture ordering and encouraged open dialogue with physicians regarding the appropriateness of urine cultures; (4) didactic and personal communications to counter long-standing myths, such as "Urine cultures always for change in mental status"; (5) a peer-review process to evaluate and justify deviations from the testing algorithm. Results: The first and second months after the introduction of the campaign, the microbiology laboratory reported 23% and 37% reductions in urine cultures ordered, respectively. During the same period, a 48% reduction in CAUTIs was reported for the entire health system. Conclusions: Reducing the number of inappropriate urine cultures is achievable with intense communication utilizing a multifaceted approach. With continued educational activities, we expect to sustain and even improve our successful reduction of inappropriate urine culture orders, ultimately improving patient outcomes. Funding: None Disclosures: None